Identification of Aves Diversity in Samudra University Area - Diyah Anjani; Adelia Putri; Lili Anna Sari Siregar; Meineta Tinambunan; Ayu Wahyuni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Birds, or avians, are living organisms classified in the animal kingdom and share characteristic features such as a body covering of feathers that enables them to fly. Birds are also a biodiversity asset that needs to be conserved and preserved due to their significance and roles in human life. Samudra University, with its expansive grounds adorned with various trees, provides a potential habitat for birds. This research, conducted in October-November 2023, aims to explore the diversity of bird species within the Samudra University area. The study employs a quantitative descriptive method, covering four locations, Location I in the Faculty of Agriculture, Location II by the sea, Location III in the Student Building, and Location IV in the Faculty of Primary School Teacher Education. The findings reveal four avian species from four families in the Samudra University area: Passer montanus, Ardea alba, Geopelia striata, and Todirhampus chloris. The avian diversity index in that area is considered moderate.